2019
DOI: 10.1080/02640414.2019.1662539
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a single night of complete and partial sleep deprivation on physical and cognitive performance: A Bayesian analysis

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRaP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Sleep disorders may influence people's daily life and give rise to many health problems. Sleep deprivation will affect humans' physical and cognitive performance [1]. Sleep apnea may cause a batch of cardiovascular consequences, such as hypertension, coronary heart disease, arrhythmia, heart failure, and stroke [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disorders may influence people's daily life and give rise to many health problems. Sleep deprivation will affect humans' physical and cognitive performance [1]. Sleep apnea may cause a batch of cardiovascular consequences, such as hypertension, coronary heart disease, arrhythmia, heart failure, and stroke [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cycling performance was harmed the next morning (08:00 h) when tested under acute sleep deprivation conditions (≤2.5 h) compared with normal sleep conditions (≥7 h) [37]; in the same study, there was a 4% decrease in 3 km cycling duration after restricting sleep. Cullen et al also reported that 15 min exhaustion cycling duration was significantly lower the morning (07:00 to 09:00 h) following 4 h of sleep [53]. Likewise, in a more than 50 min cycling experiment, insufficient sleep duration (≤4.5 h) could still impair endurance performance the next morning compared with the control sleep group (≥7 h) [54].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies reported the detrimental consequences of partial SD on sport performance in athletes [5][6][7]. For example, the mean power and peak power of a 30-s Wingate test were lower after 4 h of SD in judo competitors [8] and footballers [9].…”
Section: Introductionmentioning
confidence: 93%
“…Importantly, SD is particularly prevalent in collegiate athletes, with poor sleep quality, insufficient sleep, and daytime sleepiness commonly observed [2]. Indeed, partial SD in the nights prior to a competition is commonly observed in athletes [3][4][5] and potentially affects both physical and cognitive performance on the following day [6].…”
Section: Introductionmentioning
confidence: 99%